Optimization of selected fermentation parameters for microbial biohydrogen production using food waste as the major substrate / Nurul Azwa Binti Mohd Yunus - Nurul Azwa, Mohd Yunus (2014)

(untitled)
The energy crisis and current environmental degradation are the two vital issues for global sustainable development. Hydrogen is seen as the energy of the future; looking at the fluctuating price of oil and other natural gases prices, on top of the increasing global awareness of increasing carbon dioxide level. This carbon dioxide level is associated to global warming, acid rain and other disastrous phenomenon. Hydrogen is a sustainable energy source with minimal use of hydrocarbon. These, plus the high energy yield of 122 kJ/g makes hydrogen an attractive alternative to fossil fuels (Guo et al, 2010) The objective of this study was to find the optimum condition for anaerobic co-digestion of food waste and sewage sludge and hydrogen (H2) production. The selected parameters for optimization of hydrogen production (e.g. temperature, initial pH, inoculum size) were analysed using Response Surface Methodology with Full Factorial Design. Two types of substrates were tested; food waste as a sole substrate (Production 1) and food waste mixed with palm oil mill effluent (POME) at volume ratio 1:1 (Production 2). The optimized conditions for both Production 1 and Production 2 were pH 4.5, temperature of 35°C and inoculum size of 20%, (v/v) with maximum predicted cumulative hydrogen production (MPCHP) of 0.22 ml hydrogen /ml substrate and 0.26 ml hydrogen /ml substrate, respectively. Subsequent verification experiments at optimal parameter values yielded cumulative hydrogen of 0.28 ml hydrogen /ml substrate for Production 1 and 0.33 ml H2/ml substrate for Production 2.